Islamic perceptions of medication with special reference to ordinary and extraordinary means of medical treatment - Malik, Mohammad Manzoor (2013)
This study attempts an exposition of different perceptions of medical treatment that have emerged from the Islamic theological understanding and, at the level of appreciation, the way these perceptions contribute to diversity of views and flexible space in clinical practice. Particularly, the researcher attempts to formulate an Islamic perspective on ordinary and extraordinary means of medical treatment. The distinction is of high significance in clinical practice and its right understanding is also important to publically funded healthcare authorities, guardians of the patients, health and life insurance institutions, employers who provide health care coverage to their employees, etc. Not only these parties, but also lawyers and justice administration functionaries such as public prosecutors and judges are in need of understanding this distinction in dealing with relevant litigations. The distinction could be made in two ways regarding terminally ill patients and non-terminally ill patients separately. The factors that lead to the distinction between ordinary and extraordinary treatment are: (1) patient capacity (2) expert advice, and (3) nature of medication. Regarding terminally ill patients, medical treatment can become extraordinary because of (1) patient capacity and (2) nature of medication. In both these case the condition applies and that is expert advice taken from a group of physicians. In regards to non- terminally ill patients, extraordinary medical treatment can be understood in various ways. Three cases are very prominent: (1) treatment that is known to be useless and futile, (2) treatment that endangers the life or cause more harm than what it removes, and (3) treatment is useful, but the patient is unable to bear the cost.